2005
DOI: 10.1124/jpet.105.088948
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Na+-Ca2+Exchanger in Intracellular Ca2+Increase and Neuronal Injury Induced by Polychlorinated Biphenyls in Human Neuroblastoma SH-SY5Y Cells

Abstract: In SH-SY5Y, a human neuroblastoma cell line, Aroclor 1254 (A1254), induced a dose-dependent (10 -50 g/ml) intracellular calcium concentration ([Ca 2ϩ ] i ) increase. Two rather specific sodium-calcium (Na

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
22
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 38 publications
2
22
0
Order By: Relevance
“…As shown in Fig. 5A, the protein expression of NCX1 and NCX3 was detected in SH-SY5Y cells, which is consistent with their mRNA levels reported previously (Magi et al, 2005). On the other hand, only NCX1 protein expression was observed in LLC-PK 1 cells.…”
Section: Inhibitory Properties Of Ym-244769supporting
confidence: 80%
See 1 more Smart Citation
“…As shown in Fig. 5A, the protein expression of NCX1 and NCX3 was detected in SH-SY5Y cells, which is consistent with their mRNA levels reported previously (Magi et al, 2005). On the other hand, only NCX1 protein expression was observed in LLC-PK 1 cells.…”
Section: Inhibitory Properties Of Ym-244769supporting
confidence: 80%
“…Antisense and sense phosphorothioate oligodeoxynucleotides, which are highly specific for NCX1 or NCX3, were synthesized as reported previously Magi et al, 2005). The sequence for each isoform was as follows: NCX1: antisense, 5Ј-TGAGACTTC-CAATTGTT-3Ј; sense, 5Ј-AACAATTGGAAGTCTCA-3Ј; NCX3: antisense 5Ј-GCCATACACAAGAG-3Ј; sense, 5Ј-CTCTTGTGTATGGC-3Ј.…”
Section: Methodsmentioning
confidence: 99%
“…Although the molecular mechanisms underlying PCB-induced neurotoxicity are still poorly understood, it has been suggested that alteration of intracellular Ca 2+ homeostasis may be involved in the PCB toxic effect (Kodavanti et al, 1993;Tilson and Kodavanti, 1998;Inglefield and Shafer, 2000;Inglefield at al., 2001). In line with this hypothesis, we previously demonstrated that the inhibition of PCBinduced elevation of intracellular Ca 2+ ([Ca 2+ ] i ) results in a reduction of neuroblastoma cell death evoked by prolonged exposure to PCBs (Magi et al, 2005).…”
mentioning
confidence: 74%
“…Figure 1 shows the PCR amplification signals for NCX1, NCX2, and NCX3 and for the constitutive gene of GAPDH in two representative experiments of four preparations of HLM and monocytes. PCR fragments of the expected size (NCX1: 98 bp, NCX2: 137 bp, NCX3: 139 bp) were detected in the human neuroblastoma cell line SH-SY5Y used as a positive control [29]. cDNAs encoding for NCX1 and NCX3 were amplified in macrophages and monocytes at subsaturating cycle number (35 cycles).…”
Section: Resultsmentioning
confidence: 99%
“…BHK stably transfected with NCX1 (BHK-NCX1), NCX2 (BHK-NCX2), or NCX3 (BHK-NCX3) were grown in the same culture medium supplemented with 4% methotrexate [32]. SH-SY5Y cells were grown (371C, 5% CO 2 ) on plastic dishes in RPMI-1640 medium containing 10% FCS, 1% L-glutamine and 1% antibiotic-antimycotic solution [29]. …”
mentioning
confidence: 99%